The influence of educational leadership on students’ academic performance in secondary schools: A case of Itilima district - Ferdinandi, Catherine Mkenda; Kiwonde, Flora Mercury (SAINTIS Publishing, 2023)
This study investigated the influence of educational leadership on students’ academic performance in secondary schools. The researcher applied the descriptive research design, which allowed the in-depth study of the influence of educational leadership on students’ academic performance. The study population included 109 respondents, which comprised Heads of Schools (HoSs), Secondary Schools’ Academic Masters, discipline masters, and Ward Educational Officers (WEO). The study used a simple random and purposive sampling technique to select a sample size of 52 respondents. The researcher collected data through questionnaires. The data was analyzed by Ms-word and Ms-Excel and presented using tables. The Chi-square test and the T-test were employed in testing the association between leadership styles and students’ academic performance. The findings established that democratic leadership styles mostly influence students’ academic performance (R-value=0.932), implying that there is a strong and positive significant influence of democratic leadership styles on students’ academic achievement at a p = 0.004 level. For the laissez-faire leadership style, the relationship revealed an insignificant negative influence on students’ academic performance with a very weak relationship (R-value of 0.1) and was not significant (p = 0.072). Also, in the autocratic leadership style, although the relationship was moderate (R = 0.546), the relationship was insignificant with a p-value of 0.08. The results show that most school leaders prefer the use of democratic leadership style. The study recommends that head teachers should mostly use democratic leadership style if they want students to achieve or excel in good academic performance.